Correlation of lipid profile among patients with hypothyroidism and type 2 diabetes mellitus - Amrita Ghosh; Dipankar Kundu; Faizur Rahman; Md Ezaz Zafar; K R Prasad; H K Baruah; Tapan Mukhopadhyay (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Dyslipidemia is common metabolic abnormality in thyroid disorders overt or subclinical and diabetes mellitus (DM) with a marked increase in circulating low-density lipoprotein (LDL-C). OBJECTIVES: This study was carried out to find variations in dyslipidemic patterns in type 2 DM (T2DM) with hypothyroidism (HY). METHODS: Total cholesterol (TC), triglycerides (TG), very low-density cholesterol (VLDL), low-density cholesterol (LDL), and high-density cholesterol (HDL) were compared among the three study groups at a tertiary care teaching hospital of Bihar in eastern India. Group A: T2DM. Group B HY, and Group C: having both T2DM and HY and control group. RESULTS: The lipid profile of patients with diabetes showed TC (316.18 ± 4.299 mg/dl), TG (358.36 ± 5.544 mg/dl), LDL (214.70 ± 4.192 mg/dl), VLDL (71.67 ± 1.109 mg/dl), and HDL (29.80 ± 0.348 mg/dl). Mean lipid profile values in HYs were TC (314.38 ± 1.739 mg/dl), TG (322.46 ± 2.429 mg/dl), LDL (208.69 ± 1.665 mg/dl), VLDL (64.29 ± 0.5591 mg/dl), and HDL (41.20 ± 0.3647 mg/dl). Patients suffering from both diabetes and HY had TC (337.92 ± 4.793 mg/dl), TG (350.02 ± 5.127 mg/dl), LDL (236.17 ± 4.093 mg/dl), VLDL (70.01 ± 1.026 mg/dl), and HDL (31.74 ± 0.285 mg/dl). LDL value was markedly high in diabetic HY patients. All the lipid profile parameters were significantly increased except HDL among the patients with diabetes and HY patients. Increase was more in cholesterol and LDL values among patients suffering from both diabetes and HY. HDL levels were lowest among the patients with diabetes and also decreased among the diabetic HYs. CONCLUSIONS: In this study, on patients with diabetes and HY, dyslipidemia was more in two variables, namely, cholesterol and LDL; there was a distinct difference in lipid profile patterns between single and dual morbidities.